A survey of East Palaearctic Lycosidae (Araneae). 13. A new genus of spiny-legs Pardosinae from Eastern Kazakhstan - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2017)
A new genus, Dzhungarocosa gen. n., with three new species D. ballarini sp. n., D. omelkoi sp. n. and D. zhishengi sp. n. are described from Dzhungarian Alatau Mt. Range in South-East Kazakhstan. All species are described based on both sexes and D. omelkoi sp. n. was selected as the type species of the genus. All three species were collected among stone screes on elevations over 2900 metres. Although Dzhungarocosa gen. n. has numerous ventral tibial spines on leg I and all species inhabit stony screes like in the genera belonging to the Acantholycosa-complex, the new genus does not belong to this group.